EXTRA-TERRITORIAL TORTURE AND INHUMAN TREATMENT TOWARDS SUSPECTED TERRORISTS COMMITTED BY THE U.K. AND THE U.S. MILITARY ACTIONS - Mahfud, Mahfud (Indonesian Journal of International Law, 2014)
Since the attack to the World Trade Centre in 11 September 2001, the world has raised their awareness to any of serious allegation of terrorist activities. Many steps have been taken by the United Nations and the states to make such legislatives in their national and international level in order to prevent and combat terrorism. The world really condemns what the terrorist have done and put their maximal effort to punish them as well as to protect the innocence from experiencing such dangerous cause of such activity. The hatred of terrorists brings many actions brought by the nations, especially the United States, as a revenge of the painful feeling of those who were left by the victims. It often leads to the act of torture and inhuman treatment done by the official to the terrorist detainees. This paper will focus on the prohibition of torture and inhuman treatment both in the United States and the United Kingdom and the United States extra-territorial actions in Guantanamo Bay and Abu Ghraib prisons and also the United Kingdom’s extra-territorial conducts in treating prisoners in Iraq in relation to Al-Skeini case. Both actions of the states might be considered as a violation of national and international human rights rules because of the existence of torture in treating the terrorist detainees during their military operations. Therefore, it is important to examine whether human rights law applies extra-territorially to such violations. This study would apply the Convention Against Torture and Other Cruel Inhuman, or Degrading Treatment or Punishment (CAT) 1984, the International Covenant on Civil and Political Rights (ICCPR) 1966 and the Inter-American Commission of Human Rights (IACHR) with respect to the United States actions and the European Convention on Human Rights (ECHR) 1950, the CAT and the ICCPR for the United Kingdom’s actions.